IMPROVING TEACHER PEDAGOGICAL COMPETENCE THROUGH ELEMENTARY SCHOOL TEACHER WORK MOTIVATION - Sijabat, Desi; Sihombing, Jimmi Morgan (Sensei International Journal of Education and Linguistic, 2023)
Teacher competence will have a big influence on the creation of active, creative, effective and fun learning so that effective schools are realized.The objectives to be achieved in this study are to find out how much influence work motivation has on the pedagogical competence of teachers in the Girsang Sipanganbolon District.This study uses a quantitative approach with the type of correlational research with the population in this study are 35 teachers who are still teaching in schools.The results showed that there was an influence between the variable x (work motivation) on the variable y (pedagogic competence).The increase in work motivation is followed by an increase in the pedagogic competence of teachers.This means that for every increase in the value of work motivation by 0.776, the value of pedagogic competence will increase by 0.776.Based on the results of data analysis and hypothesis testing in this study, it can be concluded that there is an influence between teacher work motivation and teacher pedagogic competence.The pattern of influence of these two variables is stated as Y= 0.720 + 0.776x.